1998
DOI: 10.1002/(sici)1098-108x(199809)24:2<157::aid-eat5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping, and crisis support in eating disorders

Abstract: Objective Recent research has supported the role of stress in the development and maintenance of eating disorders. However, coping and crisis support, important aspects of this stress process, have received little systematic attention. The cognitive‐transactional approach to coping emphasizes the importance of the relationship between the individual and the particular problematic situation and yet most studies investigating coping in eating disorders have failed to measure situation‐specific coping. Method: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 10 publications
(17 reference statements)
6
62
1
Order By: Relevance
“…These findings parallel findings from other studies in adolescents with Type 1 diabetes but without eating problems [3,20], which have suggested that adolescents with poor adherence to diabetes management tend to use more often avoidant and negative coping strategies. In addition, findings within the eating disorders research literature have demonstrated that, when under stressful situations, young women with bulimia nervosa were more likely to blame themselves and were less likely to receive crisis support from either a partner or another very close person [21]. Women with eating disorders were more likely to use cognitive avoidance or cognitive rumination and were less likely to downplay their problems [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings parallel findings from other studies in adolescents with Type 1 diabetes but without eating problems [3,20], which have suggested that adolescents with poor adherence to diabetes management tend to use more often avoidant and negative coping strategies. In addition, findings within the eating disorders research literature have demonstrated that, when under stressful situations, young women with bulimia nervosa were more likely to blame themselves and were less likely to receive crisis support from either a partner or another very close person [21]. Women with eating disorders were more likely to use cognitive avoidance or cognitive rumination and were less likely to downplay their problems [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, findings within the eating disorders research literature have demonstrated that, when under stressful situations, young women with bulimia nervosa were more likely to blame themselves and were less likely to receive crisis support from either a partner or another very close person [21]. Women with eating disorders were more likely to use cognitive avoidance or cognitive rumination and were less likely to downplay their problems [21]. Similar findings have been also reported in other studies of young women with eating disorders, where bulimic patients were more likely to use emotional reactions, like self-blaming and escape avoidance, to reduce stress and were less likely to seek emotional support [20,36 -38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women diagnosed with eating disorders have been found to ruminate more than women without eating disorders (Troop et al 1998). In a recent longitudinal study of adolescent women, rumination was also linked to increased depressive and bulimic symptoms over time (Nolen-Hoeksema et al 2007).…”
Section: Ruminative Copingmentioning
confidence: 99%
“…To date, much of the literature on eating and coping styles addresses how maladaptive coping strategies are involved in eating disorders, such as Anorexia or Bulimia Nervosa (Troop, Holbrey, Trowler, & Treasure, 1994). Stressful life events have been implicated in the onset and maintenance of bulimia nervosa (Shatford & Evans, 1986).…”
Section: H Eating As Copingmentioning
confidence: 99%